Non-cardiac chest pain and mental health : a study among patients at the Icelandic cardiac emergency ward - Ívar Arash Radmanesh 1984- (2018)
Non-cardiac chest pain (NCCP) is a heterogeneous condition and can be defined as chest pain in the absence of cardiac causes or other acute illnesses after a medical examination has ruled them out. An estimated 50-75% of admission to cardiac emergency departments (CED) are due to NCCP. This study evaluates the frequency of non-cardiac related admissions to the CED for patients with coronary heart disease (CHD) and patients with NCCP and assesses whether adverse mental well-being is related to a higher prevalence of admissions. The study was a retrospective- and longitudinal cohort study conducted at Hjartagátt, the cardiac emergency department of Landspítali University Hospital, Reykjavik, Iceland. Participants were 504 patients (18 – 65 years) presenting with chest pain to the cardiac emergency department from October 2015 to November 2016. Measurements included questionnaires assessing somatic symptoms and mental well-being and information-provision gathered from the medical records of participants. Non-cardiac related admissions were prevalent among patients admitted to the CED. Overall, 66% of participants (333) belonged to the NCCP group compared to 22% (112) in the CHD group. Non-cardiac related admissions were also high among patients with CHD (70%). More anxiety and health anxiety were related to a higher frequency of non-cardiac related admissions for patients with no cardiac diseases. Interventions that focus on physical and mental causes of pain might prove useful for this group of patients. Keywords: non-cardiac chest pain, coronary heart disease, mental well-being, nccp, chd, Heildartexti og beiðni um lokun